Copeptin Levels in Patients With Acute Ischemic Stroke and Stroke Mimics. Issue 9 (September 2015) - Wendt, Matthias; Ebinger, Martin; Kunz, Alexander; Rozanski, Michal; Waldschmidt, Carolin; Weber, Joachim E.; Winter, Benjamin; Koch, Peter M.; Nolte, Christian H.; Hertel, Sabine; Ziera, Tim; Audebert, Heinrich J.
Abstract : Background and Purpose—: Copeptin levels are increased in patients diagnosed with stroke and other vascular diseases. Copeptin elevation is associated with adverse outcome, predicts re-events in patients with transient ischemic attack and is used in ruling-out acute myocardial infarction. We evaluated whether copeptin can also be used as a diagnostic marker in the prehospital stroke setting. Methods—: We prospectively examined patients with suspected stroke on the Stroke Emergency Mobile—an ambulance that is equipped with computed tomography and point-of-care laboratory. A blood sample was taken from patients immediately after arrival. We analyzed copeptin levels in patients with final hospital-based diagnosis of stroke or stroke mimics as well as in vascular or nonvascular patients. In addition, we examined the associations of symptom onset with copeptin levels and the prognostic value of copeptin in patients with stroke. Results—: Blood samples of 561 patients were analyzed. No significant differences were seen neither between cerebrovascular (n=383) and other neurological (stroke mimic; n=90) patients ( P =0.15) nor between vascular (n=391) and nonvascular patients (n=170; P =0.57). We could not detect a relationship between copeptin levels and time from onset to blood draw. Three-month survival status was available in 159 patients with ischemic stroke. Copeptin levels in nonsurviving patients (n=8: median [interquartile range], 27.4 [20.2–54.7] pmol/L) were significantly higher than in surviving patients (n=151: median [interquartile range], 11.7 [5.2–30.9] pmol/L; P =0.024). Conclusions—: In the prehospital setting, copeptin is neither appropriate to discriminate between stroke and stroke mimic patients nor between vascular and nonvascular patients. Clinical Trial Registration—: URL: http://www.clinicaltrials.gov. Unique identifier: NCT01382862. The Pre-Hospital Acute Neurological Therapy and Optimization of Medical Care in Stroke Patients study (PHANTOM-S) was registered (NCT01382862). This sub-study was observational and not registered separately, therefore. Abstract : Supplemental Digital Content is available in the text.